ANALISIS MENGENAI ALASAN PENGGUNAAN INTERNET MASYARAKAT SUMATERA SELATAN - Oktaf Juairiyah (MULTITEK INDONESIA, 2020)
Along with the advancement of information technology, many needs depend on internet usage. A study of the reasons and places of the community in accessing the internet is needed. The methodology used in this study is descriptive analysis in regencies/cities in South Sumatra. The results obtained were above 85% of the population above 5 years in the Regency / City to access the internet at home for various reasons. Social media, entertainment and as a place of information are the biggest reasons people access the internet. There is a connection between the reason and the place where residents access the internet in the Regency / City of South Sumatra Province.